2015
DOI: 10.1002/wps.20199
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of deep transcranial magnetic stimulation for major depression: a prospective multicenter randomized controlled trial

Abstract: Major depressive disorder (MDD) is a prevalent and disabling condition, and many patients do not respond to available treatments. Deep transcranial magnetic stimulation (dTMS) is a new technology allowing non-surgical stimulation of relatively deep brain areas. This is the first double-blind randomized controlled multicenter study evaluating the efficacy and safety of dTMS in MDD. We recruited 212 MDD outpatients, aged 22-68 years, who had either failed one to four antidepressant trials or not tolerated at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
284
2
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 334 publications
(305 citation statements)
references
References 27 publications
9
284
2
10
Order By: Relevance
“…Research that is representative of the efficacy demonstrated in a pivotal multicenter study of the first conventional rTMS device (which uses the figure-of-eight coil) was relegated to subjects who failed a single antidepressant 15 ; whereas the pivotal study performed for dTMS demonstrated efficacy for patients with 1-4 failed medication trials 13 .…”
Section: Representative Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Research that is representative of the efficacy demonstrated in a pivotal multicenter study of the first conventional rTMS device (which uses the figure-of-eight coil) was relegated to subjects who failed a single antidepressant 15 ; whereas the pivotal study performed for dTMS demonstrated efficacy for patients with 1-4 failed medication trials 13 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…The field maps are adjusted for stimulator power output level required to obtain 120% of the hand motor threshold. This figure is from Rosenberg, Shoenfeld, Zangen, Kotler, and Dannon, 2010 13 . Please click here to view a larger version of this figure.…”
Section: Representative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When conventional treatments for depression are ineffective, patients with depression are increasingly turning to TMS for treatment, especially because it is devoid of the cognitive side-effects associated with ECT. There are now two devices with distinct coil designs, the conventional figure (Levkovitz et al, 2015;O'Reardon et al, 2007). As well as an expansion in available coils, TMS is also being used increasingly off-label, including for indications other than major depressive disorder and for medication-resistant depression in children, which is reviewed in Magavi, Reti, and Vasa (2017) in this Special Edition.…”
Section: Editorialmentioning
confidence: 99%